Tres métodos para la determinación cuantitativa del alcohol etílico - Morales R., C.; Greene, G. L. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Quantitative measurements of ethyl alcohol in biological materials present several methodological problems with respect to specificity and precision. Three different methods are examined in this study, and the range and utility of ech is discussed